About Possible Urbanism. Conversation with Fernando de Terán - Monclús, Javier (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
Fernando de Terán, a prominent urban planner (1934, architect, ETSAM 1961), is considered a reference in theoretical reflection on Spanish urban planning in recent decades. Due to his work in the administration and his work in the history of urban planning, he is recognized as a protagonist and an exceptional witness of the attempts to control the development of Spanish cities during the 20th century. His long career and extensive experience guarantee first-hand knowledge of a complex process that we thought was appropriate to bring here to reflect on habitat from an urban perspective.
Keywords: Urban Planning Theory; History of Urban Planning; Housing Estates